(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Objective: To determine the effectiveness of TB DOTS program in Isfandyar Bukhari District (IBD) Hospital Attock Study Design: Observational study Duration of Study: January 2021 to July 2021 Place of Study: Isfandyar Bukhari District (IBD) Hospital Attock Materials and Methods: A total of 678 TB patients, presenting to TB DOTS Centre through OPD or referred from health care centers, after confirmation of diagnosis were registered with DOTS program and enrolled in the study. Informed consents were taken after explaining study procedure to patients. A validated questionnaire was used to collect the information about patients like demography, clinical presentation, diagnosis, treatment compliance and outcome. All these information were entered in the TB card and handed over to patients for follow up. Data was entered in SPSS software for analysis. Results: A total of 678 TB patients enrolled in the study, consisting of 294 (43%) males and 384 (67%) females were followed up for treatment outcomes. Treatment outcome is an indicator for the effectiveness of national TB control programs. Out of 678 patients, 259 (38%) were smear positive, 307 (45%) were sputum smear negative and 112 (17%) were extra pulmonary cases. After 6 months follow up of every patient, 163 patients were declared cured,409 completed treatment and seven died due to any reason during study. Two patients lost to follow up. Cure rate was 84.3%. Conclusion: The overall treatment success rate was 84.3%, which was lower than the globally set target of 90% for 2025. The overall treatment success rate is satisfactory but still needs to be improved to achieve the international targeted treatment outcome.